Ecological and Economic Significance of Mangroves: A Comprehensive Review - K, Abduljaleel; Prakash, P S; KT, Manjula; PV, Mini (Aquatic Life Sciences, 2026)
Mangrove ecosystems, distributed across tropical and subtropical coastlines, are globally recognized for their exceptional biodiversity and multifunctional ecological roles. They sustain coastal fisheries by serving as breeding and nursery habitats, support diverse terrestrial and aquatic fauna, enhance shoreline stability through wave attenuation and erosion control, and improve water quality via nutrient recycling and pollutant filtration. Mangroves are also among the most efficient blue carbon sinks, contributing significantly to climate-change mitigation. From a socio-economic perspective, they provide timber and non-timber resources, support artisanal fisheries, enable ecotourism-based livelihoods, and hold high potential for carbon-credit revenue and bioprospecting. The review synthesizes evidence from 135 studies published between 1990 and 2024, retrieved from Web of Science, Scopus, Google Scholar, and institutional repositories, based on their relevance to mangrove ecology, ecosystem services, and community-level economic benefits. Only peer-reviewed articles, technical reports, and case studies with clear methodological descriptions were included. The synthesis reveals that the ecological and economic functions of mangroves are strongly interdependent, with degradation of habitat quality directly reducing fisheries productivity, carbon storage efficiency, and livelihood security. The review highlights the urgent need for integrated management approaches, including hydrological restoration, community-based conservation, and policy-supported payment-for-ecosystem-services mechanisms, to enhance ecosystem resilience under accelerating anthropogenic and climate pressures.